A distal regulatory element regulates Wx gene expression and the amylose content in rice - Yang, Qingqing; Dong, Fuhua; Zhu, Wenjie; Zhao, Dongsheng (Frontiers in Plant Science, 2025)
Granule-bound starch synthase I (GBSSI) is encoded by the Waxy (Wx) gene, which is responsible for amylose biosynthesis and is an important factor determining rice cooking and eating quality in rice grains. Although some studies have edited the promoter of Wx to fine-tuning gene expression level and amylose content, few studies have focused on the distal allelic variations of Wx. In this study, we identified and confirmed one distal cis-regulatory element (CRE) related to the Wx gene. Furthermore, the cre mutants were generated in the Nipponbare background carrying the Wxb or Wxa allele. The amylose content of Wxb-cre mutant decreased by 21.43%–31.51% compared with that of wild-type rice with the Wxb allele. However, no significant difference in amylose content was observed between wild-type plants and Wxa-cre mutants which carried the Wxa allele. The altered mature mRNA transcript and protein level of Wx gene caused by CRE showed a high consistency with their amylose content. Meanwhile, lower gelatinization temperature and final viscosity were found in the Wxb-cre mutants, whereas the grain shape and chalkiness and major agronomic traits were not affected. Possibly, the cre mutant causes the transcriptional reprogramming of starch metabolism. Overall, we identified a distal CRE to finely regulate the Wx gene expression and amylose content, which provided a potentially useful allele for quality improvement in rice breeding.